On some identities involving certain Hardy sums and Kloosterman sum - Dağlı, M. C. (Ukrains’kyi Matematychnyi Zhurnal, 2020)
UDC 511We give a new reciprocity theorem for the Hardy sum $s_{5}(h,p).$ Also, a hybrid mean value problem involving the Hardy sum $s_{4}(h,p)$ and Kloosterman sum is studied and two exact computational formulae are obtained.